(untitled) (Bangladesh Journal of Plant Taxonomy, 2009)
The species richness of cyanobacteria belonging to the family Chroococcaceae in rice fields of North Bihar, India was studied over a 60-day period. Twenty-eight species representing nine genera were identified. The highest number of 21 species was observed around 30th day against eight and 13 species around 10th and 60th day of rice cultivation, respectively. Aphanocapsa grevillei (Hass.) Rabenh., Aphanothece naegelii Wartm and Microcystis marginata (Menegh.) Kützing were observed from 10th to 60th days of rice cultivation. Keywords: Chroococcaceae; Cyanobacteria; Rice cultivation; North Bihar; India. DOI: 10.3329/bjpt.v16i1.2747 Bangladesh J. Plant Taxon. 16(1): 57-63, 2009 (June)